Access to benznidazole for Chagas disease in the United States-Cautious optimism? - Jonathan D Alpern; Rogelio Lopez-Velez; William M Stauffer (PLoS Neglected Tropical Diseases)
Drugs for neglected tropical diseases (NTD) are being excessively priced in the United States. Benznidazole, the first-line drug for Chagas disease, may become approved by the Food and Drug Administration (FDA) and manufactured by a private company in the US, thus placing it at risk of similar pricing. Chagas disease is an NTD caused by Trypanosoma cruzi; it is endemic to Latin America, infecting 8 million individuals. Human migration has changed the epidemiology causing nonendemic countries to face increased challenges in diagnosing and managing patients with Chagas disease. Only 2 drugs exist with proven efficacy: benznidazole and nifurtimox. Benznidazole has historically faced supply problems and drug shortages, limiting accessibility. In the US, it is currently only available under an investigational new drug (IND) protocol from the CDC and is provided free of charge to patients. However, 2 companies have stated that they intend to submit a New Drug Application (NDA) for FDA approval. Based on recent history of companies acquiring licensing rights for NTD drugs in the US with limited availability, it is likely that benznidazole will become excessively priced by the manufacturer-paradoxically making it less accessible. However, if the companies can be taken at their word, there may be reason for optimism.